The causes and consequences of the growth of informal settlements in ward six and seven of Epworth. - Masimba, Julianos (Midlands State University, 2017)
The increase in demand for housing not matching with housing delivery have been the major cause for the growth of informal settlements in most urban areas especially on the peripheries of these towns. Epworth as the only settlement which the government accepted and recognised after independence as an informal settlement have seen a drastic increase on population into the informal settlements and the study will focus on ward six and seven which have been the mainly affected wards in wards in Epworth. In 2005, the government embarked on operation Murambatsvina as way to bring orders in most urban areas by getting read of illegal structures but this brought about suffering to a number of urban population as they were left homeless. This had a negative impact on satellite town were those affected migrate to this town like Epworth as people looked for what termed to be cheap life and most came from Harare into these already existing informal settlements. Also the study is going to look into poverty as of the major driver for the growth of informal settlement in Epworth were due to high prices for land in urban areas has led to people finding their own ways of providing themselves with roof over their head. Poverty levels are very high in these two wards which confines them to absence of opportunities accompanied by high levels of malnourishment, illiteracy, hunger, lack of education and social instability and this is characterised by a chronic shortage of economic, social and political participation, relegating individuals to exclusion as social beings and these are some of the challenges which are going to be discussed this research. However it should be noted that the purported community housing initiatives have been politicised in Epworth and most urban areas and have led to the growth of informal settlement. Lands for future development by local authorities have been invaded by these termed housing cooperative which are linked to political parties and meant to push forward political agendas all in the name of empowerment through land allocations for housing but later they have turned to be form informal settlement as no services will be offered neither servicing by responsible authorities. Others which the research is going to look into are migration where people due to economic hardships have migrate into Epworth in search of cheap life where rental are low as compared to Harare. The research will also look into possible solutions to the challenges and the solution come from those which would have suggested in data collection and analyses. The role of local authorities is also going to be scrutinized as it seems that they have sleeping on duty failing to manage urban planning and have been overridden by land barons and politics of the area. The statutes that govern urban planning will also be analysed and see if they also have a role in the growth of the informal settlements. All these and more are going to be looked into in this research.